2021
DOI: 10.1002/kin.21476
|View full text |Cite
|
Sign up to set email alerts
|

Lumped kinetic simulation of hydrodenitrogenation for full‐range middle‐low temperature coal tar

Abstract: With the increasingly prominent environmental problems and depletion of light petrochemical resources, the clean utilization of heavy oil has become the research focal area. The hydrodenitrogenation (HDN) experiments and kinetics of full‐range middle‐low temperature coal tar (MLCT) was studied on a fixed‐bed reactor with a Ni‐Mo/γ‐Al2O3 catalyst. Two kinds of three‐lumped kinetic models (K1 and K1.24) based on different reaction orders and high‐middle‐low reactivities were established and fitted by a simulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…Some examples of the alternative sources of diesel fuel precursor streams are MDSO, middle-low temperature coal tars (MLCT), heavy gas oils from oil sands bitumen (HGOSB), VGO, LCO, and CGO. It has been observed that these types of feedstocks tend to have a higher content of heterocyclic N-containing compounds, aromatics, and asphaltenes compared with conventional middle distillates such as SRGO, resulting in the need for more severe operating conditions, more HDN active catalyst, and better kinetic models. For these reasons, the kinetics of ultradeep HDT reactions of heterocyclic N-containing compounds has attracted greater interest in several research groups in recent years, leading to the development of better and more detailed kinetic models for HDN, HDA, HDO, etc.…”
Section: Hydrodenitrogenation Reactionsmentioning
confidence: 99%
“…Some examples of the alternative sources of diesel fuel precursor streams are MDSO, middle-low temperature coal tars (MLCT), heavy gas oils from oil sands bitumen (HGOSB), VGO, LCO, and CGO. It has been observed that these types of feedstocks tend to have a higher content of heterocyclic N-containing compounds, aromatics, and asphaltenes compared with conventional middle distillates such as SRGO, resulting in the need for more severe operating conditions, more HDN active catalyst, and better kinetic models. For these reasons, the kinetics of ultradeep HDT reactions of heterocyclic N-containing compounds has attracted greater interest in several research groups in recent years, leading to the development of better and more detailed kinetic models for HDN, HDA, HDO, etc.…”
Section: Hydrodenitrogenation Reactionsmentioning
confidence: 99%